2024
DOI: 10.1021/jacs.4c00382
|View full text |Cite
|
Sign up to set email alerts
|

Running Wild through Dirhodium Tetracarboxylate-Catalyzed Combined CH(C)-Functionalization/Cope Rearrangement Landscapes: Does Post-Transition-State Dynamic Mismatching Influence Product Distributions?

Wentao Guo,
Dean J. Tantillo

Abstract: A special type of C–H functionalization can be achieved through C–H insertion combined with Cope rearrangement (CHCR) in the presence of dirhodium catalysts. This type of reaction was studied using density functional theory and ab initio molecular dynamics simulations, the results of which pointed to the dynamic origins of low yields observed in some experiments. These studies not only reveal intimate details of the complex reaction network underpinning CHCR reactions but also further cement the generality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…The M06 functional gives results very similar to those of B3LYP-D3, which has been extensively used for dirhodium reactions. 33,35,39 Single point energies were also calculated using M06 with the larger def2-TZVP basis set. Stationary points were categorized as a potential energy minimum or first-order saddle point by analyzing the vibrational frequencies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M06 functional gives results very similar to those of B3LYP-D3, which has been extensively used for dirhodium reactions. 33,35,39 Single point energies were also calculated using M06 with the larger def2-TZVP basis set. Stationary points were categorized as a potential energy minimum or first-order saddle point by analyzing the vibrational frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…While this work was under review, Tantillo reported a similar discovery for the reaction with 1,3-cyclohexadiene. 35 Analysis of motion during these reaction trajectories revealed that C–H insertion is the dynamically direct pathway from the nonstatistical entropic intermediate, and for the Cope product to be formed there must be synchronization of the Cope vibrational mode along with several vibrational modes for carbon atom bending. Overall, this analysis illustrates the possibility of identifying key motion in an entropic intermediate that influences product selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…While it is difficult to imagine how such a complex system could be manipulated through rational catalyst design, characterization of its dynamic behavior at least opens the door to doing so, e.g., one can imagine constructing catalyst binding sites that hinder certain vibrations. For example, for Davies and co-workers′ CHCR reactions promoted by Rh 2 (s-DOSP) 4 (Figure ), which favor CHCR products over others and do so with high stereoselectivity, we suspect that the shape of the catalyst binding site preferentially accommodates a [Rh] carbene conformation that has dynamical tendencies that favor formation of the desired products over formation of the putative competing intermediate …”
Section: Dynamical Distractions?mentioning
confidence: 99%
“…Wide hollow arrows correspond to pathways for which transition structures were located. Reproduced from ref . Copyright 2024 American Chemical Society.…”
Section: Dynamical Distractions?mentioning
confidence: 99%
“…While these nonstatistical situations have been identified in several different types of organic reactions (e.g., substitution, addition, pericyclic, , and rearrangement ) it is only recently that they have begun to be discovered in organometallic reactions . Examples include the dynamic merging of reaction steps in alkene hydrogenation by a Ru-hydride, reaction pathway bifurcation , in Rh-carbene, Au-vinylidene, and Au-carbene reactions, and roaming/unexpected intermediates during Pd transmetalation and Ni cross-coupling reactions …”
Section: Introductionmentioning
confidence: 99%